2013
DOI: 10.12957/jbrastele.2013.8167
|View full text |Cite
|
Sign up to set email alerts
|

Atrasos Nos Encaminhamentos De Pacientes Com Suspeita De Câncer Bucal: Percepção Dos Cirurgiões-Dentistas Na Atenção Primária À Saúde

Abstract: Resumo Objetivos: Verificar quais as possíveis razões que justifiquem o atraso da chegada do paciente com câncer bucal aos setores de maior complexidade de atenção em saúde. Materiais e métodos: O estudo teve como público-alvo cirurgiões-dentistas atuantes em Atenção Primária à Saúde formalmente vinculados ao Projeto TelessaúdeRS (276 potenciais participantes). Foi utilizado um questionário hospedado em software de questionários online, com o link para acesso disponibilizado por correspondência eletrônica e at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 3 publications
0
7
0
11
Order By: Relevance
“…Há estudo utilizando a visão do dentista sobre a atenção a saúde (32,33) , demonstrando que a perspectiva desse profissional é importante para o melhor entendimento da realidade do serviço. O presente estudo pretende auxiliar na questão do acesso aos serviços públicos pelos PNE.…”
Section: Discussionunclassified
“…Há estudo utilizando a visão do dentista sobre a atenção a saúde (32,33) , demonstrando que a perspectiva desse profissional é importante para o melhor entendimento da realidade do serviço. O presente estudo pretende auxiliar na questão do acesso aos serviços públicos pelos PNE.…”
Section: Discussionunclassified
“…Measures such as conducting routine preventive exams for early detection and active search of the population most likely to develop the disease are prescribed in the main guiding documents of primary oral health care actions in Brazil 18,36,37 . Studies with dental surgeons from PHC in the state of Rio Grande do Sul have identified that the professionals interviewed presented a high degree of understanding about their responsibilities for the control of oral cancer 38,39 .…”
Section: Cad Saúde Pública 2019; 35(12):e00014319mentioning
confidence: 99%
“…The most important aspect to be considered is related to the coverage of primary dental care and the number of SDC, as they are still far from covering the entire population 19 . Other barriers, such as the lack of professional training, temporary employment, unfavorable work conditions and difficulties to effectively conduct a multidisciplinary teamwork 38,44,45 , as well as the unequal geographical distribution of the existing DSC 46 , are mentioned.…”
Section: Cad Saúde Pública 2019; 35(12):e00014319mentioning
confidence: 99%
“…This delay has been associated with the patient's late search for services, and the health system's low responsibility to provide users with comprehensive care 10 . Studies that sought reasons related to the organization of the health system directed the analysis towards specific programs 11 or professional perception regarding the problem 12,13 , unrelated to the policies in force and the available structure.…”
Section: Introductionmentioning
confidence: 99%